2023
DOI: 10.3390/pathogens12030413
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Economic Cost Analysis of Microbial Keratitis from a Tertiary Referral Hospital in Australia

Abstract: Microbial keratitis is the most common cause of infective vision loss. The causative organism varies by region, and most cases require intensive antimicrobial therapy. The purpose of this study was to analyse the causative organisms of microbial keratitis, its presentation and economic burden from a tertiary referral hospital in Australia. A retrospective review of 160 cases of microbial keratitis was performed, over a 5-year period from 2015–2020. A wide variety of costs were considered to determine the econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…In the current study, of the 72% pathogenic bacteria which isolated from corneal specimens collected from target students, 42% were Staphylococcus aurous, 22% coagulase negative staphylococci, 6% Streptococcus species and 2% were Pseudomonas species. The results of this present study were similar to other studies conducted in Sana'a and Taiz cities in Yemen (20,21), as well as studies conducted in UK (22) and Australia (23). Other studies reported dissimilar results, Hossein Hatam et al, 2021 and F Stapleton et al, 2012 showed that, the most common isolated bacteria were Pseudomonas aeruginosa and the next common organism was Staphylococcus species especially coagulasenegative species (3,24,25).…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, of the 72% pathogenic bacteria which isolated from corneal specimens collected from target students, 42% were Staphylococcus aurous, 22% coagulase negative staphylococci, 6% Streptococcus species and 2% were Pseudomonas species. The results of this present study were similar to other studies conducted in Sana'a and Taiz cities in Yemen (20,21), as well as studies conducted in UK (22) and Australia (23). Other studies reported dissimilar results, Hossein Hatam et al, 2021 and F Stapleton et al, 2012 showed that, the most common isolated bacteria were Pseudomonas aeruginosa and the next common organism was Staphylococcus species especially coagulasenegative species (3,24,25).…”
Section: Discussionsupporting
confidence: 89%
“…Low resistance rates in S. pneumoniae have also been reported in other studies, for example, in an Australian study that investigated the epidemiology of microbial keratitis, and in a nationwide study in the USA (Antibiotic Resistance Monitoring in Ocular Microorganisms-ARMOR) that monitored the development of resistance between 2009 and 2018 [12,13]. The isolates from the susceptibility study of the Paul-Ehrlich-Society 2019-2020 were also 100% susceptible to levofloxacin [8].…”
Section: Streptococcus Pneumoniaementioning
confidence: 77%
“…A novel antiviral agent, SC93305, reportedly showed effectiveness against acyclovir-resistant strains of HSV-1 & HSV-2; SC93305 also reportedly did not interfere with host humoral immune responses[ 181 ]. Amentoflavone was found to inhibit resistant strains of HSV-1 including HSV-1/106, HSV-1/153, and HSV-1/blue by interfering with early-stage transcription of viral genes[ 182 ].…”
Section: Antiviral Therapy For Herpes Simplex Keratitis: Efficacy And...mentioning
confidence: 99%